Respuesta :
Answer: p=-7
Step-by-step explanation:
To solve for p, you want to isolate the variable, get p alone. You would use different algebraic properties to do so.
30+6p=7p+42-5
30+6p=7p+37
-7=p
p=-7
Answer:
p = -7
Explanation:
Step 1 - You should start by expanding the problem. To that simply multiply the seven by p + 6
30 + 6p = 7(p + 6) - 5
30 + 6p = 7p + 42 - 5
Step 2 - Simplify (subtract 5 from 42)
30 + 6p = 7p + 42 - 5
30 + 6p = 7p + 37
Step 3 - Subtract 30 from both sides of the equation
30 + 6p = 7p + 37
30 - 30 + 6p = 7p + 37 - 30
6p = 7p + 7
Step 4 - Subtract 7p from both sides of the equation
6p = 7p + 7
6p - 7p = 7p - 7p + 7
6p - 7p = 7
Step 5 - Subtract 7p from 6p
6p - 7p = 7
-p = 7
Step 6 - Make the variable positive
-p = 7
-p • -1 = 7 • -1
p = -7
Therefore, p = -7
p = -7
Explanation:
Step 1 - You should start by expanding the problem. To that simply multiply the seven by p + 6
30 + 6p = 7(p + 6) - 5
30 + 6p = 7p + 42 - 5
Step 2 - Simplify (subtract 5 from 42)
30 + 6p = 7p + 42 - 5
30 + 6p = 7p + 37
Step 3 - Subtract 30 from both sides of the equation
30 + 6p = 7p + 37
30 - 30 + 6p = 7p + 37 - 30
6p = 7p + 7
Step 4 - Subtract 7p from both sides of the equation
6p = 7p + 7
6p - 7p = 7p - 7p + 7
6p - 7p = 7
Step 5 - Subtract 7p from 6p
6p - 7p = 7
-p = 7
Step 6 - Make the variable positive
-p = 7
-p • -1 = 7 • -1
p = -7
Therefore, p = -7